A Study on the Presence of Iranian Researchers in Academic Social Networks: A Case Study on the Faculty Members of Semnan University of Medical Sciences, Iran - Narges Ghorbani; Marjan Momeni; Raheb Ghorbani; Fahimeh Babalhavaeji (مدیریت اطلاعات سلامت, 2018)
Introduction: Scientific social networks increase the speed of ‎data transfer through increasing the interaction among researchers in one hand, and result in their dynamism and identification and their scientific ‎productions on the other hand. With regard to the importance of the presence of researchers in such networks, the aim of this study was to investigate the presence and the use of such networks by the faculty members of Semnan University of Medical Sciences, Semnan, Iran.